Application of Flipbook-Based E-book Learning Media on Basic Football Passing Skills - Diah Arum Purweni; Mochamad Ridwan (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2026)
This study explores the use of Flipbook-based E-book learning media to teach Basic Football Passing Skills. It aims to help junior high school Physical Education, Sports, and Health (PJOK) teachers present football passing material in a more creative and engaging way, making it easier for students to learn these skills. Flipbook-based e-books combine text, images, and interactive features to create a modern learning experience that can increase students' interest. The research used a quantitative experimental method to measure the impact of this media by collecting and analyzing numerical data. The findings showed that the average pretest score was 10.5, while the posttest average was 15.5. The t-test result was 0.000, which is less than 0.05, showing a significant difference between pretest and posttest scores. In summary, Flipbook-based E-book learning media for Basic Football Passing Skills has a positive effect on the learning outcomes of grade VIII students.